Opinions of Scientists About the Deixis Phenomenon - Khalikova Latofat Uktamovna; Mustafayeva Kamola Nuriddin kizi (Genius Journals, 2022)
In speech activity there is always a need to connect the linguistic form with reality and to express a personal attitude to it. The execution of the same tasks is the responsibility of the deictic means. The original Greek meaning of the word "deixis" is "show", "sign", in scientific usage it means "point to reality", "show".
Keywords: Linguistic structures; indexicalls; dexters; classification